2021
DOI: 10.1016/j.drudis.2021.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, inflammation, and the adiponectin paradox: Therapeutic targets in SARS-CoV-2

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 65 publications
2
14
0
Order By: Relevance
“…Many studies have shown that the accumulation of DAMPs is one of the important causes of aging-related damage [25]. TLR4 is a predominant DAMP sensor that has been proven to mediate inflammation in many cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the accumulation of DAMPs is one of the important causes of aging-related damage [25]. TLR4 is a predominant DAMP sensor that has been proven to mediate inflammation in many cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a link between 'adiponectin paradox' and SARSCoV2 infection and its chronic complications has also been demonstrated lately [221]. Curiously, antagonistic pleiotropy was found.…”
Section: Facets Of Adiponectin Paradoxmentioning
confidence: 98%
“…Accordingly, SARSCoV2 may aug ment both chronic inflammation and adiponectin serum levels and this plays a beneficial role contributing to more efficient combating acute infection in younger ages rep resenting a kind of hormesis. Conversely, in aging popu lation SARSCoV2 induction of 'adiponectin paradox' is detrimental [221].…”
Section: Facets Of Adiponectin Paradoxmentioning
confidence: 99%
“…Ho et. al found that aging and comorbidities augment risk the of ARDS in COVID-19, and SARS-CoV-2-induced inflammation can cause IR and APN paradox ( Ho et al, 2021 ). Therefore, inhibition of APN paradox-mediated inflammation could be beneficial in this regard ( Ho et al, 2021 ).…”
Section: Role Of Apn In Sars-cov-2 Infectionmentioning
confidence: 99%